La morte per acqua. Iconografia di un thiasos marino su un frammento di sarcofago inedito del Museo Civico Giovanni Marongiu, Cabras (OR) - Ciro Parodo (Layers. Archeologia Territorio Contesti, 2018)
Abstract: This study concerns an unpublished fragment of a marble sarcophagus decorated with a scene of sea thiasos, now in the warehouses of the Museo Civico Giovanni Marongiu at Cabras (OR). By means of the iconographic analysis of this image, the aim of this paper is to investigate its meaning in the Roman funeral sculpture and consequently as well the social and cultural dynamics that have determined its use by the patronage.